Pengaruh Harga, Diskon, dan Promosi terhadap Keputusan Pembelian pada Live Streaming Shopee di Kota Jambi - Aulia Firanti; Nurlia Fusfita (ARZUSIN, 2025)
The advancement of digital technology has driven significant changes in consumer behavior, including among Generation Z in Indonesia. In this context, e-commerce platforms such as Shopee have utilized live streaming features as an interactive marketing strategy to enhance purchase decisions. This study aims to examine the influence of price, discount, and promotion on consumer purchase decisions via Shopee’s live streaming feature in Jambi City. A quantitative approach was employed using a survey method. Data were collected through the distribution of Likert-scale questionnaires to 100 Generation Z respondents who are active Shopee users in Jambi. Data analysis was conducted using multiple linear regression with SPSS version 30. The results indicate that, partially, the variables of price and promotion have a positive and significant effect on purchase decisions, while discounts do not show a significant influence. Simultaneously, all three variables collectively have a significant effect on purchase decisions. These findings underscore the importance of competitive pricing strategies and effective promotions in enhancing the appeal of live streaming features, and contribute to the development of more responsive digital marketing strategies tailored to the preferences of young consumers.